Sustainability and competitiveness in the hospitality industry - Costa, Vânia Gonçalves, 1978-; Costa, Carlos, 1964- (Advances in hospitality, tourism, and the services industry book series., 2022)
"This book addresses essential questions related to hospitality businesses' sustainable development and business planning models' aims from various points of view, concentrating on planning in this industry in the context of tourism destination management and development"--